Discrete element method simulation of disc type furrow openers in paddy soil - Ahmad, Fiaz; Qiu, Baijing; Ding, Qishuo; Ding, Weimin; Khan, Zahid Mehmood; Shoaib, Muhammad; Chandio, Farman Ali; Rahim, Abdur; Khaliq, Abdul (International Journal of Agricultural and Biological Engineering, 2020)
For granular materials, discrete element modeling is one of the best computer tools to simulate their behavior and interactions. A field experiment was carried out to evaluate the performance of disc furrow openers in paddy soil. Discrete element simulation was done to develop a 3D DEM model for notched, toothed and double disc furrow openers using EDEM software. Hertz Mindlin contact model with bonding was applied for simulation to fulfill the obligations of the soil moisture and bonding between the cohesive particles. Simulated and field experimental data were compared to determine the applicability in the different working conditions. The results of the simulation validated the applicability of the Hertz-Mindlin contact model with bonding to simulate the no till paddy soil using an extremely narrow tillage tool. The calibrated value of normal and shear stiffness was 5×107 N/m, and the calibrated value of bond normal and shear strength was 3×107 Pa. The relative error (–1.7% to 20.6%) for the double disc furrow opener was lower as compared with that notch typed (29.2% to 44.4%) and toothed type (31.5% to 45.9%) furrow openers.Keywords: soil tillage, discrete element method, discrete element modeling, furrow opener, paddy soilDOI: 10.25165/j.ijabe.20201304.4800Citation: Ahmad F, Qiu B J, Ding Q S, Ding W M, Khan Z M, Shoaib M, et al. Discrete element method simulation of disc type furrow openers in paddy soil. Int J Agric & Biol Eng, 2020; 13(4): 103–110.